Array - Sakdiyah, Hidayanti; Wahyuningsih, Fahmi (LATERNE, 2021)
From the result of interview found some problems in speaking skill. Those problems occur in X- Sprache Class in MAN Bangkalan. There are some problems, namely 1) students are not brave to speak German or to express their opinion, 2) students are still minimal in mastering German vocabulary, 3) students are still less motivated in learning foreign languages. Therefore the writer offers a learning technique or method to faciliate students in understanding of learning material. Autogrammj?gerspiel is one of learning technique that can train speaking skill of student.The problem statement in this article is how the Autogrammj?ger spiel matches with the German speaking skill. The purpose of discussion in this article is to describe the compatibility of the Autogrammj?ger spiel with German speaking skill for theme Schule (school) and subtheme Gegenst?nde in der Schule (objects at school) in X- Sprache Class in MAN Bangkalan. The focus of discussion in this article is limited only to the suitability of the Autogrammj?gerspiel with German speaking skill for student in X Sprache Class with theme school and subtheme objects at school in MAN Bangkalan. The Method used in this article is literature study. It means writer takes several sources in the form (comparison thinking and analysis from experts) and the results of a questionnaire from a German language teacher. The results of the discussion in this article can be concluded that the Autogrammj?gerspiel with German speaking skill has a good compatibility. That result get from the questionnaire from German teacher who has a presentage 93,3 % of 100 % . Besides this result is also reinforced by some thoughts from experts and relevant data which proves that the Autogrammj?gerspiel is matched with German speaking skill. Keywords: Autogrammj?ger,game technique, speaking skill